(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the types of adjunct constructions, in particular dynamic and static adjunct constructions. The article also thoroughly studies the semantic-syntactic type of content of dynamic and static adjunct elements, their definitions given by linguists. The ideas about “Adjunct constructions” presented below are of scientific and theoretical importance and are of great importance for the development of other linguistic disciplines.